THE CAUSES OF POLITICAL INSTABILITY IN THE REPUBLIC OF TURKEY - S. B. Druzhilovsky (Vestnik MGIMO-Universiteta, 2016)
The article examines the causes of the permanent political instability in the Turkish Republic, which leads to frequent change of governments, degradation of political parties and changing of policies. On the example of the activities of different cabinets it is showen that the basis of their instability is the frequent creation of coalition governments consisting of parties that stand on different ideological positions. Inter-party antagonism, in its turn, is a consequence of the split of the Turkish society along civilizational, ethnic and religious grounds, which determines the different political orientation of the various layers of the Turkish society. At the same time the article shows the examples of the undoubted efficiency of one-party governments, however they never get support from the opposition parties, and eventually also fail to effectively and consistently implement their proposed policies. The author also deals with a policy of the ruling today in Turkey, the Islamist Party of Justice and Development, which after several years of successful political and economic reforms to date entered the period of deep crisis and is increasingly losing its authority and influence both in Turkey and in neighboring countries.